Introduction to Policing - Cox, Steven M. (SAGE Publications, Inc. (US), 2023)
Written by an author team that includes former and current law enforcement officers, Introduction to Policing focuses on the most thought-provoking, contemporary issues in the world of policing. The authors tackle complex issues that impact policing today, such as social diversity; advancements in technology; and global issues, such as terrorism and transnational organized crime. The Fifth Edition offers fully updated content in SAGE’s Vantage courseware platform.